Association between psychosocial safety climate and job demand resources towards burnout among community college staff in Peninsular Malaysia - Chang, Vui Seng Wilson (2019)
Psychological hazards are one of the relevant areas in occupational health with many studies done on occupational stress. However, the extreme end of mental health which is burnout that has a more serious impact has not been much explored. Previous study has shown that 10 to 15% of the working population in the Netherlands suffer from the burnout that has a more detrimental effect compared to occupational stress. Therefore in this study, it was proposed that Psychosocial Safety Climate (PSC) act as a precursor to working conditions and its effects on employees’ psychological well-being. Furthermore, PSC will decrease emotional exhaustion, particularly through job demands (bullying and emotional demands), and job resources (i.e social support). A cross-sectional survey was conducted and respondents were sampled through multistage sampling were based on the number of community colleges in Peninsular Malaysia, approximately 50 colleges were first randomly chosen and later staff from each selected colleges were further sampled through simple random sampling. Finally, a total of 425 employees from 45 organizations agreed to participate in the study. For statistical analysis, Hierarchical Linear Modeling software was used as it is able to test a multilevel relationship. It was found that PSC was negatively associated with workplace bullying (γ = -.13, SE = .03, P<.001) and emotional demands (γ = -.17, SE = .05, P<.01) and positively associated with social support (γ = .16, SE = .02, P<.001). In addition, the relationship between PSC with burnout was mediated by workplace bullying (ƶ=- 3.61, SE=.01, p<.001), emotional demands (ƶ=-3.18, SE=.01, p<.001) and social support (ƶ=-6.86, SE=.01, p<.001). In conclusion, these finding on PSC would provide community colleges staff a better guidance and understanding about the concepts of PSC to improve the psychological health especially with regards to burnout.